Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian M.; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; Philipp, Hanna; Kladt, Carolin; Schrauder, Michael G.; Weingärtler, Stefan; Hanf, Volker; Hartmann, Arndt; Rübner, Matthias; Schneider, Holm; Lelieveld, Jos; Beckmann, Matthias W.; Wurmthaler, Lena A.; Fasching, Peter A.; Schneider, Michael O. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting.Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan–Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator.Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10 – 0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%.Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patientsʼ labour.
Keywords: SARS-CoV-2; COVID-19; pregnancy; prevalence; infection